Evaluating the effectiveness of city-level Islamic economic coordination in advancing Sharia financial inclusion in Bandar Lampung - Albab, Ulil; Mawardi, Mawardi (Universitas Islam Indonesia, 2025)
IntroductionIslamic financial inclusion has increasingly been promoted as a strategic instrument for inclusive economic development, particularly in emerging economies where micro, small, and medium enterprises play a central role in employment creation and poverty reduction. In Indonesia, the establishment of regional Islamic economic coordination bodies represents a policy effort to strengthen local Islamic financial ecosystems. Nevertheless, empirical evaluations of how such institutions operate and contribute to Islamic financial inclusion at the city level remain limited, especially outside major metropolitan areas.ObjectivesThis study aims to evaluate the effectiveness of a city-level Islamic economic coordination program in enhancing Islamic financial inclusion. It specifically examines the roles of Islamic financial literacy initiatives, access to Sharia-compliant financing, post-financing assistance, MSME clustering, and institutional governance in shaping inclusion outcomes.MethodThe study adopts a qualitative descriptive approach using an effectiveness evaluation framework. Data were collected through semi-structured interviews with key stakeholders, including program administrators, Islamic financial institutions, local government officials, and MSME beneficiaries, complemented by document analysis of policy reports and program records. Thematic analysis was employed to identify patterns related to program implementation, institutional capacity, and observed outcomes.ResultsThe findings indicate that the program generated positive short-term outcomes, including increased awareness of Islamic finance, improved access to Sharia-compliant financing, and the initiation of Sharia-based MSME clusters. However, overall effectiveness was constrained by limited post-financing assistance, uneven capacity-building, weak institutional coordination, and the absence of a systematic monitoring and evaluation framework. Access to financing alone did not consistently translate into sustainable MSME growth without continuous mentoring and institutional support.ImplicationsThe results highlight that effective Islamic financial inclusion requires an integrated approach combining financial literacy, financing, capacity-building, and strong local governance. For policymakers, the study underscores the importance of strengthening institutional mandates, allocating dedicated resources, and developing evidence-based monitoring systems to enhance program sustainability and impact.Originality/NoveltyThis study contributes original empirical evidence from a subnational context by linking institutional governance analysis with MSME-level outcomes. It advances the literature on Islamic financial inclusion by demonstrating how city-level coordination bodies shape inclusion effectiveness and by emphasizing the value of effectiveness evaluation frameworks in Islamic economic governance.